(untitled) (Interdisciplinary Studies Journal, 2024)
This article explores the role of local communities in the sustainability of tourist destinations, highlighting the benefits and challenges of integrating community participation in sustainable tourism development. The research employs a theoretical-exploratory approach, based on a systematic and critical review of existing literature, to identify gaps and formulate new hypotheses on community involvement in tourism. The study reveals that the inclusion of local communities is essential for ensuring environmental preservation, cultural appreciation, and social equity, promoting tourism that meets both the needs of tourists and the aspirations of host communities. The Community-Based Tourism (CBT) model is presented as a viable solution for balancing economic, social, and environmental interests, emphasizing self-management, cooperativism, and active community participation.